2019
DOI: 10.1016/j.cjtee.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Do we really need to repair the pronator quadratus after distal radius plating?

Abstract: PurposeFractures of distal radius are one of the common orthopaedic injuries. Placing the plate on volar surface requires release of underlying pronator quadratus (PQ) muscle. No consensus is present in the literature about the repair or not of the PQ. The purpose of this study was to evaluate the influence of PQ repair on functional outcome and complications.MethodsRetrospectively 83 patients of distal radius fractures managed with volar plating between 2014 and 2016 were evaluated. Demographic data, operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…We excluded two studies from the Cochrane Central Register of Controlled Trials database, one master's thesis, which is a review article from the CNKI database, and one RCT that compared PQ repair with no PQ repair with only 3 months of follow-up. Therefore, the meta-analysis included five RCTs [8,10,[18][19][20] and six retrospective case-control studies [7,[21][22][23][24][25].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded two studies from the Cochrane Central Register of Controlled Trials database, one master's thesis, which is a review article from the CNKI database, and one RCT that compared PQ repair with no PQ repair with only 3 months of follow-up. Therefore, the meta-analysis included five RCTs [8,10,[18][19][20] and six retrospective case-control studies [7,[21][22][23][24][25].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Most studies presented the number of fractures in each AO Foundation/Orthopaedic Trauma Association (AO/OTA) fracture classification [26], except one study [23] that did not report the included fracture types. Two studies analyzed the outcomes of patients with DRF AO/OTA types B and C [22,25] with or without PQ repair instead of the pooled outcomes.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Some authors claim that patients experience an early effect of PQ repair. In a retrospective study of 63 patients, Pathak et al reported improved pain relief and ROM at four weeks, and improved grip strength at three months in the repair group [ 21 ]. We could not confirm these early findings in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may be more important to consider the Soong index in accurate plate positioning as this has been shown to correlate to the rate of plate removal and tendon damage. 12 - 14 Additionally, Parthak et al 15 found in the early postoperative period that PQ repair may result in reduced pain levels which may be from protecting these tendons in the early postoperative period. Overall, RCTs may not be appropriate to assess the potential benefit of plate coverage as they may be drastically underpowered to assess this uncommon but clinically important complication, large-scale population-based studies thus may be more appropriate.…”
Section: Discussionmentioning
confidence: 99%